2016
DOI: 10.1016/j.joca.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Charge based intra-cartilage delivery of single dose dexamethasone using Avidin nano-carriers suppresses cytokine-induced catabolism long term

Abstract: Objective Avidin exhibits ideal characteristics for targeted intra-cartilage drug delivery: its small size and optimal positive charge enable rapid penetration through full-thickness cartilage and electrostatic binding interactions that give long half-lives in-vivo. Here we conjugated Avidin with dexamethasone (DEX) and tested the hypothesis that single-dose Avidin-delivered DEX can ameliorate catabolic effects in cytokine-challenged cartilage relevant to post-traumatic OA. Methods Avidin was covalently conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 40 publications
6
132
0
Order By: Relevance
“…Frequent injections are painful, costly and inconvenient to the patients and also cause local joint and systemic toxicity. It is critical to develop therapies that can target the affected tissue inside the knee joint, bind there and provide a sustained drug release over several weeks following their intra-articular administration [37]. In vitro, the difference between administering a single injection of a conjugated and unconjugated drug can be modeled.…”
Section: Drug Release Profilesmentioning
confidence: 99%
See 4 more Smart Citations
“…Frequent injections are painful, costly and inconvenient to the patients and also cause local joint and systemic toxicity. It is critical to develop therapies that can target the affected tissue inside the knee joint, bind there and provide a sustained drug release over several weeks following their intra-articular administration [37]. In vitro, the difference between administering a single injection of a conjugated and unconjugated drug can be modeled.…”
Section: Drug Release Profilesmentioning
confidence: 99%
“…For example, recently it was shown that the effect of, dexamethasone (DEX) was time dependent and short lived in rescuing the IL-1α induced catabolic activity in vitro [37]. By 12 days of culture, the effect of single dose DEX had tapered off in suppressing the loss of sulfated glycosaminoglycans (sGAG) compared to the continuous dose DEX condition [37].…”
Section: Drug Release Profilesmentioning
confidence: 99%
See 3 more Smart Citations